Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Rokok Pada Usia Remaja Di Kabupaten Rembang - Achmad Yoki Febrima; Dian Imami Mashuri; Nur Wulan Intan Palupi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The aim of this research is to find out which factors are most important for buyers of cigarette products, including advertising, price, culture and psychology. In this study, the population who consumed cigarette products were 100 teenagers aged 17 to 21 years. This research is quantitative. The results of research data analysis show that factors such as advertising, price, culture and psychology have a significant influence on the decisions of teenage cigarette buyers. Advertising has a significant influence of 31.6% on the decision of buyers of cigarette products, and other variables not examined in this study accounted for 68.4% of the total.